Psychological preparation for dental treatment in children: A randomized clinical study (Research, Society and Development, 2021)
Objective: to evaluate the psychological preparation in children submitted to dental treatment and to correlate anxiety and fear between children and their parents. Method: randomized clinical study with 26 children divided into two groups, a control group (CG) and an intervention group (IG). The randomized subjects in the IG went through psychological preparation, initially with the presentation of the office, materials and instruments, stimulating their manipulation and clarifying doubts and curiosities about the procedures. Subsequently, the instructional therapeutic toy (ITT) technique was used, first with the story telling “Tigger goes to the dentist” and, later, the subjects dramatized the dentist's role. The CG received the usual treatment at the clinic, based on the talk-show-do technique. Data were collected using two questionnaires, the Children’s Fear Survery Schedule Dental Subscale applied to children, and the CORAH scale applied to parents, both pre and post the procedure. Results: the IG initially presented an average in the anxiety and fear score of 29.1% and after the intervention of 21.5%, demonstrating statistical significance, the CG before the procedure obtained 27.3% and subsequently 23.2%. The classification of the level of anxiety decreased significantly in both groups, comparing the moments before and after, resulting in 88.5% with low level of anxiety and 11.5% with average level. There was no significant correlation between children's anxiety with their parents. Conclusions: it is evident that there are interdisciplinary strategies that reveal more humane paths in the production of health and education and the intervention of psychological preparation and ITT can be applied in other health environments.